Un hombre del 87: Juan Hernández López - Todd, Roberto H. (My University, 1935)
Un hombre del 87: Juan Hernández López
Keywords: Hernández López, Juan; Malaret, Pedro; Baldorioty de Castro, Román, 1822-1889; Porrata Doria, Luis, 1845-1925; Carbonell, Celedonio; Monclova Gallardo, Pedro; Valle Atiles, Pedro del